KEMAMPUAN BERTAHAN HIDUP TRICHODERMA HARZIANUM DAN TRICHODERMA VIRENS SETELAH DITUMBUHKAN BERSAMA DENGAN JAMUR PATOGEN TULAR TANAH SECARA IN VITRO - Rina Sriwati; T. Chamzurni; L. Kemalasari (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2014)
The experiment was conducted at the Laboratory of Plant Pathology Faculty of Agriculture, Syiah Kuala University from February to June 2013. The purpose of study was to evaluate the survival of T. harzianum and T. virens after cohabiting with soil borne pathogenic fungi (Fusarium sp, Rhigidoporus sp, and Sclerotium sp) as well as the type of interaction. Trichoderma fungi and fungal pathogens were grown on PDA in vitro, and then observed their growth after being reisolated on 3 different growth zones. The results showed that T. harzianum and T. virens growing with Fusarium sp were capable to grow over the space. It was evident from the results of reinoculation on a petridish B (border zone) and C (zone Trichoderma) colonies, that T. harzianum and T. virens regrew, while the pathogens were not able to regrow. When cohabiting with Sclerotium sp and Rhigidoporus sp, antagonistic fungus regrew after reisolation but pathogens also grew on Petridis B (border zone). It indicates that on the contact area (petri dish B), Sclerotium sp and Rhigidoporus sp conduct defense over the competition. Regrowth of fungal pathogens on contact area (border) indicates that the fungus has a high level of competition. Antagonist agents such as T. virens and T. harzianum were able to survive and regrow after cohabiting with fungal pathogens and showed type A interaction (against Fusarium sp), while cohabiting with Sclerotium sp and Rhigidoporus sp showed the type B interaction.